The Impact of Diversified Assessment Methods on Student Performance and Engagement in College Classrooms - Khabeb Sulaiman; Rauf El-Nasir (PT Mutiara Bustan Ilmu, 2025)
The implementation of diversified assessment methods has emerged as an innovative strategy to enhance the effectiveness of student evaluation in higher education. This study aims to analyze the impact of various assessment approaches—including project-based assessments, peer assessments, digital self-tests, blended assessments, mobile-enhanced evaluations, and co-designed rubrics—on student academic performance and engagement. A mixed methods approach was employed, combining quantitative data from engagement questionnaires, academic scores, and digital learning logs with qualitative insights obtained through semi-structured interviews with students and instructors. Statistical analyses such as t-tests and Pearson correlations were used alongside thematic analysis for qualitative data. Preliminary findings indicate that diversified assessment methods contribute positively to student motivation, conceptual understanding, and active classroom participation. Moreover, student engagement significantly improves when assessments are supported by timely feedback, transparent rubrics, and opportunities for students to co-design evaluation criteria. These findings offer valuable recommendations for higher education institutions seeking to develop fair, inclusive, and meaningful assessment strategies that foster deep learning and student success.